Close-coupling calculations of elastic and inelastic positron-helium scattering - Chaudhuri, P.; Adhikari, S. K. (Iop Publishing Ltd, 1999)
Elastic and inelastic positron-helium scattering have been investigated in different partial waves at medium energies using the close-coupling approximation with realistic wavefunctions employing the following states: He(1s1s), He(1s2s), He(1s2p), He(1s3s), He(1s3p), Ps(1s), Ps(2s) and Ps(2p). All excitations of the helium atom are in the spin-singlet electronic state. Calculations are reported of cross sections to He(1s1s), He(1s2s), and He(1s2p) transitions for incident positron energies up to 200 eV. These cross sections are in good agreement with experimental results.